Strategic Financial Management in a Dynamic Economy: Optimizing Investment, Mitigating Risks, and Leveraging Financial Technology for Corporate Sustainability - Natser, Muhammad (Golden Ratio of Data in Summary, 2025)
Financial management plays a fundamental role in corporate sustainability, influencing investment decisions, risk mitigation, and long-term financial stability. This study examines the strategic importance of financial management in enhancing corporate performance, emphasizing the impact of capital structure optimization, risk management frameworks, and financial technology integration. Drawing from financial theories and empirical evidence, the research highlights the significance of balancing debt and equity financing, utilizing financial derivatives to manage risk exposure, and adopting technological advancements such as artificial intelligence and blockchain for financial decision-making. The study further explores the role of financial governance, liquidity management, and ethical financial practices in fostering investor confidence and regulatory compliance. Findings suggest that firms with proactive financial strategies exhibit greater resilience against economic uncertainties and market fluctuations, achieving sustainable growth and competitive advantage. The study contributes to the existing literature on corporate financial management by providing insights into effective financial planning and decision-making frameworks. The implications extend to corporate managers, policymakers, and financial institutions in developing adaptive financial policies that align with evolving economic and technological landscapes.